Hsp90 is essential for restoring cellular functions of temperature-sensitive p53 mutant protein but not for stabilization and activation of wild-type p53: implications for cancer therapy - Müller, Petr; Ceskova, Pavla; Vojtesek, Borek (The Journal of biological chemistry, 2005)
Several signaling pathways that monitor the dynamic state of the cell converge on the tumor suppressor p53. The ability of p53 to process these signals and exert a dynamic downstream response in the form of cell cycle arrest and/or apoptosis is crucial for preventing tumor development. This p53 function is abrogated by p53 gene mutations leading to alteration of protein conformation. Hsp90 has been implicated in regulating both wild-type and mutant p53 conformations, and Hsp90 antagonists are effective for the therapy of some human tumors. Using cell lines that contain human tumor-derived temperature-sensitive p53 mutants we show that Hsp90 is required for both stabilization and reactivation of mutated p53 at the permissive temperature. A temperature decrease to 32 degrees C causes conversion to a protein conformation that is capable of inducing expression of MDM2, leading to reduction of reactivated p53 levels by negative feedback. Mutant reactivation is enhanced by simultaneous treatment with agents that stabilize the reactivated protein and is blocked by geldanamycin, a specific inhibitor of Hsp90 activity, indicating that Hsp90 antagonist therapy and therapies that act to reactivate mutant p53 will be incompatible. In contrast, Hsp90 is not required for maintaining wild-type p53 or for stabilizing wild-type p53 after treatment with chemotherapeutic agents, indicating that Hsp90 therapy might synergize with conventional therapies in patients with wild-type p53. Our data demonstrate the importance of the precise characterization of the interaction between p53 mutants and stress proteins, which may shed valuable information for fighting cancer via the p53 tumor suppressor pathway.
Keywords: Gene Expression Regulation, Neoplastic; Temperature; mutace; Neoplasms; Cell Line, Tumor; proteiny tepelného šoku HSP90; Transcription, Genetic; regulace genové exprese u nádorů; protoonkogenní proteiny c-mdm2; Proto-Oncogene Proteins; jaderné proteiny; nádorový supresorový protein p53; Proto-Oncogene Proteins c-mdm2; Feedback, Physiological; zpětná vazba fyziologická; HSP90 Heat-Shock Proteins; genetická transkripce; lidé; konformace proteinů; Humans; nádory; Protein Conformation; teplota; Mutation; nádorové buněčné linie; Nuclear Proteins; Tumor Suppressor Protein p53; protoonkogenní proteiny